Anolis boulengerianus Thominot, 1887, a senior synonym of Anolis isthmicus Fitch, 1978 (Squamata: Dactyloidae) - de Oca, Adrián Nieto-Montes; Köhler, Gunther; Feria-Ortiz, Manuel (Zootaxa, 2014)
For most of its history, the name Anolis boulengerianus Thominot, 1887 has been regarded as a junior synonym of Anolis nebulosus (Wiegmann, 1834) or Anolis nebuloides Bocourt, 1873. However, a comparison of the syntypes and additional topotypical specimens of A. boulengerianus with three topoparatypes and additional specimens of the species currently referred to as Anolis isthmicus Fitch, 1978 showed that these two names pertain to the same species. Because of the priority principle, A. isthmicus becomes a junior synonym of A. boulengerianus. We provide a redescription of the type series of A. boulengerianus and an updated diagnosis for this taxon relative to all other beta anoles.